1990
DOI: 10.2105/ajph.80.9.1116
|View full text |Cite
|
Sign up to set email alerts
|

A population-based descriptive study of housefire deaths in North Carolina.

Abstract: We report a population-based study of housefire deaths in North Carolina in 1985 using data obtained from fire investigators and the North Carolina medical examiner system. The crude death rate was 3.2 per 100,000 population; age-specific death rates were highest for ages 75-84 years. Death rates for Whites were one-third as high as death rates for other races. Of those decedents tested for alcohol, 56 percent had blood alcohol levels -22 mmol/L. Most fatal fires were caused by heating units or cigarettes. (Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…This is consistent with studies done by Ambade and Godbole (2006), Gupta and Srivastava (1988), Chawla et al (2010), Gupta et al (1993) and Khartade et al (2014). On the contrary, study done by Patetta and Cole (1990) reported burns by heating instrument in 33% cases, smoking in 26% and cooking in 9% of the cases. The differences in observations may be due to different geographical areas and extent of awareness about safety measures.…”
Section: Discussionmentioning
confidence: 86%
“…This is consistent with studies done by Ambade and Godbole (2006), Gupta and Srivastava (1988), Chawla et al (2010), Gupta et al (1993) and Khartade et al (2014). On the contrary, study done by Patetta and Cole (1990) reported burns by heating instrument in 33% cases, smoking in 26% and cooking in 9% of the cases. The differences in observations may be due to different geographical areas and extent of awareness about safety measures.…”
Section: Discussionmentioning
confidence: 86%
“…18 Fire-related deaths are lowest in the summer and highest during the winter, due to increased use of heating and ignition sources, 19 particularly portable space heaters and wood-burning stoves. 20 Fatal fires usually occur at night or early in the morning, when victims may be sleeping and unaware that a fire is taking place or too confused to respond in time to escape. 4 Substandard and unsafe dwellings, whether in rural or urban areas, are less likely to have fire warning systems and exits 7 and, according to Greenberg and Schneider, 21 as marginal environments, elevate the risk of fire deaths by arson.…”
Section: Introductionmentioning
confidence: 99%
“…The inconvenience of accessing and repeatedly activating the button prompts many adults to simply disconnect the batteries or remove the detector. 12 The high percentage of alcohol involvement among adult victims who die in house fires (85% of victims who died in cooking-related fires were legally impaired in one study) 13 suggests another possible reason for impatience with hush buttons. Also, people with impaired judgment may activate the hush button in the event of an actual fire, negating the earlywarning opportunity.…”
mentioning
confidence: 96%